Teknik Penerjemahan Bahasa Arab ke Bahasa Indonesia: Taqniyyāt al-Tarjamah min al-‘Arabiyyah ila al-Indūnīsiyyah - Istiqomah, Salma Nur; Nurhaliza, Tria Novia; Nafis, Zain; Supriadi, Rinaldi (Study Program of Arabic Language Teaching, 2023)
This research aims to discover the translation techniques used to translate Arabic into Indonesian. This type of research is qualitative research that uses a descriptive approach. The data taken are various techniques used in Arabic-Indonesian translation. The data source we took was from the literature which refers to sources relevant to the discussion. Data analysis is carried out using content analysis, namely reviewing the data obtained and grouping the required data. The results of this research showed that there were 18 translation techniques used to transfer Arabic into Indonesian. Using appropriate translation techniques can ensure that the original meaning of the source text is well preserved in the translation. To ensure the accuracy and quality of the translation, translators must be flexible and creative in choosing translation techniques that suit the characteristics of each text.